Improving calorie and muscular endurance knowledge through MiPlato FIT flashcards among collegiate students - Md Radzi, Noor Azila Azreen; Mazaulan, Mardiana; Zamri, Fatin Nur Shahira; Abu Kassim, Nurul Ain; Raja Hussain, Raja Nurul Jannat; Mohamed, Muhamad Noor; Syed Mud Puad, Sharifah Maimunah; Shari, Maisarah (Academica Press Solutions, 2024)
More than half of screened Malaysians are overweight or obese, largely due to excessive calorie intake and insufficient physical activity. Many lack knowledge about food calorie content and suitable exercises for weight loss. The MiPlato FIT flashcards, an upgraded version of MiPlato, focus on healthy eating and balanced diets, aiming to improve nutrition education through interactive methods. Recognizing the critical role of food calorie intake and physical activity in energy balance, MiPlato FIT introduces a new feature: guidance on performing simple exercises to reduce calorie consumption. In response to the widespread lack of awareness about calorie counting and effective reduction methods, the game encourages participants to strategically place low-calorie food cards and prioritize physical activity cards indicating calorie expenditure. Moreover, participants engage in 30-second exercises with proper technique. Given Malaysia's high obesity rates in Asia, MiPlato FIT flashcards could enhance nutrition education and emphasize the importance of exercise in calorie reduction. Results show a significant increase ($p<0.05$) in participant knowledge of calorie counting for various food groups and exercise movements after engaging in the MiPlato FIT flashcard game. These findings suggest that MiPlato FIT is a highly effective tool for conveying information about calories and physical activity, promoting awareness of healthy eating habits and lifestyle choices.